The Chilean Network of Microbial Culture Collections: Establishment and Operation (Boletín Micológico, 2016)
According to the data available at the World Data Center for Microorganism-WDCM from the Word Federation for Culture Collection-WFCC, Chile has four registered culture collections that preserve 2777 microbial strains. At the global point of view, the culture collections in Chile are in different level of operation regarding its own infrastructure and compliancy with quality standards for preservation of strains and for services provide. The absence of funding to support the preservation of the Chilean microbial assets is a key issue for the development of the Chilean bioeconomy. Considering this, the Chilean culture collections started working together to establish the Chilean Network of Microbial Culture Collections (RCCCM, acronym in Spanish). In this note, the establishment and operation of the RCCCM is presented and discussed.